A PdAg-CeO2 nanocomposite anchored on mesoporous carbon: a highly efficient catalyst for hydrogen production from formic acid at room temperature. Issue 37 (10th September 2019) - Zhang, Zhujun; Luo, Yixing; Liu, Shiwen; Yao, Qilu; Qing, Shaojun; Lu, Zhang-Hui
Abstract : Herein, CeO2 -modified PdAg alloy nanocomposites were anchored on mesoporous carbon, showing exceedingly high catalytic activity for HCOOH dehydrogenation at room temperature. Abstract : The efficient and selective dehydrogenation of formic acid by a robust solid catalyst at room temperature is highly attractive for a fuel cell-based hydrogen economy but still very challenging. Although significant progress has been achieved in the development of heterogeneous catalysts, their catalytic performance remains inadequate. Herein, we report a facile and surfactant-free method for the anchoring of the PdAg-CeO2 nanocomposite (3.6 nm in diameter) onto mesoporous carbon (denoted as PdAg-CeO2 /MC). The optimized PdAg-CeO2 /MC catalyst exhibited an exceedingly high catalytic activity (turnover frequency, 2272.8 h −1 at 303 K and 5275.5 h −1 at 333 K) with a 100% hydrogen selectivity, among the highest catalytic performances reported to date for all heterogeneous catalysts for formic acid dehydrogenation. Systematic studies indicated that strong synergistic interactions between PdAg-CeO2 nanocomposites and the MC host were realized due to the presence of amorphous CeO2 with abundant oxygen vacancies for coordination; the excellent catalytic results indicated more possibilities for the effective application of formic acid as a promising hydrogen storage material.